PEMELIHARAAN DAN KELANCARAN PROSES PRODUKSI BERPENGARUH TERHADAP KUALITAS PRODUK DI CV VANNISA BROWNIES - Joval Ifghaniyafi; Dudi Haryadi (Lembaga Penelitian Universitas Langlangbuana, 2020)
The purpose of this study was to find out how maintenance, smooth production processes, and the quality of products that exist in CV Vannisa Brownies. And to find out how much influence the maintenance of product quality, the effect of the smooth production process on product quality and the effect of maintenance and smooth production processes on product quality. In this study, the independent variable (X) is the maintenance and smoothness of the production process, while the dependent variable (Y) is the quality of the product. Product quality greatly affects the entire organization from suppliers to customers and from maintenance to the production process. Product quality is a strategic thing to maintain and improve if you want to do business in the long run. Companies that can meet expected product quality are companies that can meet customer expectations. Product quality can be supported by several factors, including the maintenance and smooth production process. This research is population research. Using a questionnaire with the number of respondents in this study were 23 employees. The analytical method used is a quantitative method with descriptive analysis and verification analysis. To process data, the author uses the help of Microsoft Excel 2016 and SPSS 25 For Windows. The results of the study stated that the implementation of maintenance was in a fairly good category, the implementation of the smooth production process was in a fairly good category, the implementation of product quality was in a fairly good category. Maintenance affects the product quality by 72.53%, the smoothness of the production process affects the quality of the product by 8.05%, and the maintenance and smoothness of the production process affect the quality of the product by 80.6%. While the results of the T-Test show that maintenance has an effect on product quality, the smooth production process does not significantly influence product quality. The F-test shows that the maintenance and smoothness of the production process affect the quality of the product. To achieve quality products that are targeted by companies, they should pay more attention to the maintenance and smoothness of the production process together. Because both aspects play an important role in supporting the quality of the products produced.